IMPLEMENTATION OF CHARACTER EDUCATION IN THE 2013 CURRICULUM - Hamriana Hamriana; Sida Sida; Muhajir Muhajir (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Character education is not a new thing in the world of education today. Character education requires educators to fully contribute to instilling character values to create a cultured nation in the 2013 curriculum. This study describes character education in the 2013 curriculum in elementary schools cluster I, bontomarannu sub-district, Gowa regency, South Sulawesi. This research is qualitative research with a case study approach. The results showed that the implementation of character in the 2013 curriculum, which consists of being religious, honest, disciplined, hard work, and responsible, is still lacking and still needs to be re-evaluated. Some factors support and hinder the creation of character education in the 2013 curriculum, which is eroded and can change if every component such as teachers, students and society work well together.